ANALISIS POTENSI PENERIMAAN PAJAK DAERAH KOTA BUKITTINGGI - Daniati Puttri (Jurnal Apresiasi Ekonomi, 2016)
The purpose of this research is to examine and analyze the potential tax revenue of Bukittinggi. To determine the revenue potential requires a research data using time series. Research using time series will help see how potential acceptance of any local taxes. The research used descriptive method quantitative and quanlitative, the research sources by collecting data, presenting and explaining the data through the numbers. Analysis by calculation of the potential local tax revenues based on the potential of the area, realization of acceptance, make comparisons with the regulations, see trend growth and how the projections in the future. The results found out of 11 (eleven) types of local taxes stipulated in Law No. 28 of 2009, which has been levied by the Bukittinggi as much as eight (8) types of local taxes. Potential local tax revenue of Bukittinggi in 2015 were mainly derived from hotel taxes. Keywords: Local Tax Revenues, Potential of local tax, Projections